MENELAAH HUKUM JUAL BELI TERHADAP HARTA WARISAN YANG BELUM DIBAGI: TINJAUAN HUKUM ISLAM - Mustafa Mustafa (AL-ILMU, 2023)
This article conducts an analysis of the legal aspects of buying and selling inherited assets that have not been distributed, specifically focusing on Islamic law. The complexities of transactions involving undistributed inherited assets pose challenges within Islamic inheritance law, encompassing legal, ethical, and equitable considerations. Using an analytical approach, the article explores the relevant legal regulations in Islamic law concerning the buying and selling of undistributed inherited assets. This includes examining concepts of inheritance, property rights, asset distribution, and the principles that govern such transactions. The analysis sheds light on the obstacles and factors to consider in the practice of buying and selling undistributed inherited assets. The article highlights the implications of prohibitions or restrictions on these transactions from a legal standpoint. The aim of this analysis is to provide a deeper understanding of the Islamic legal regulations pertaining to the buying and selling of undistributed inherited assets. It emphasizes the importance of adhering to Islamic legal principles and ethical considerations to ensure fairness and validity in asset distribution. In summary, this article offers a concise analytical overview of the legal implications surrounding the buying and selling of undistributed inherited assets within Islamic law. It aims to provide guidance and enhance understanding for individuals and communities engaged in such transactions, while considering the relevant principles of Islamic law. Keywords: Law, Buying and selling, Inheritance